The Origin of Written Laws in Ancient Greece - Marcheva, Deyana (Yearbook of the Law Department, 2019)
The article addresses the question how and why do written laws come into being in Ancient Greece in the archaic period from the mid seventh century BC. The research delves into different types of historical sources including stone inscriptions and literary works so that to illuminate fragments and details of how the people reflect on the necessity and significance of written laws. The assumption is that there is no one general explanation why people started to write down the laws. In Ancient Greece the general lasting rules that we call today laws were first denoted with the term “thesmos”, and later with the term “nomos”. In any case, the first written laws were publicly acknowledged and announced as a guarantee against the arbitrary power.